POLICY SERIES: CONGRESSIONAL UPDATE - Lindberg, B W (Innov Aging, 2018)
This popular annual session will provide cutting-edge information on what the 115th Congress has and has not accomplished to date, and what may be left for the lame duck session to address. Speakers will discuss key issues such as Social Security, Medicare, Medicaid, and the Older Americans Act, and how older adults rate the importance of various issues. Predictions for the 116th Congress will abound. Feel free to come and add your challenges and prophecies to the list. Hill staffers, advocates, and lobbyists will present. B. W. Lindberg, The Gerontological Society of America, Washington, District of Columbia, United States E. Solway, University of Michigan, Ann Arbor, Michigan, United States S. Khasawinah, U.S. Senate Special Committee on Aging, Washington, District of Columbia, United States